Cooperative indexing in U.P Diliman Library system with implications to the Index to Philippine Periodicals (IPP) a basis for an action plan - Manaay, Lyle D. (2002)
The study sought to find out what seems to be the prevailing problem of cooperation among the U.P. Diliman Library system and what measures can be adopted to alleviate problems posed by librarians tasked with indexing Philippine Periodicals. Twenty-three out of 27 librarians from 24 libraries of the U.P. Diliman Library system responded to the survey.